(RETRACTED) INFORMATION LITERACY: AN ALTERNATIVE TO SUPPORT LEARNING OUTCOMES IN BIOLOGICAL STUDENTS - Sari, M S; Sunarmi, Sunarmi; Sulasmi, E S; Wicaksono, R S; Sudrajat, A K (Unnes Science Education Journal, 2019)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).